Awareness of TMJ disorders among Indian population - Rupawat, Divya; Sivaswamy, Vinay; Minal Gopal, Tulsani; Devi N, Sanjana; Ganapathy, Dhanraj (International Journal of Psychosocial Rehabilitation, 2020)
Background: Temporomandibular disorders (TMDs) represent a group of orofacial pain disorders that cause structural and functional changes in the temporomandibular joints and related structures. Prevalent clinical signs include pain, tenderness upon palpation, limited range of movement, and clicking sounds. A correct diagnosis and treatment will resolve pain over time in most cases. Long-standing TMD without a correct diagnosis and treatment can sometimes give rise to chronic or persistent pain. This study aims to evaluate the awareness of TMJ disorders among the Indian population.